Future Thinking among twelfth grade students in Government schools in Sultanate of Oman in Light of Some Variables - Al-Kharusi, Issa Khamis Ali (Journal of Educational and Psychological Sciences, 2023)
The aim of the current study was to investigate the degree to which 12 grade students in government schools in Oman possess future thinking skills. The study used a descriptive approach through the application of a questionnaire consisting of 23 items distributed across four skills: future planning, future problem-solving, future imagination, and future anticipation. It was administered to a sample of 312 male and female students in government schools in Oman. The mean and standard deviation of the sample's responses were calculated, and the t-test was used to compare the means of the study sample according to the variable of the type of the gender (male-female) and specialization (pure-applied) variables.The results showed that the level of future thinking skills among students in government schools in Oman, in general, was high. The levels of the skills of future planning, future problem-solving and future imagination were high, while the level of future anticipation skill was moderate within the study sample. Additionally, the results showed no statistically significant differences at the (0.05) in the levels of future thinking skills among twelfth-grade students in government schools in Oman attributed to the gender. However, statistically significant differences at a significance level of (0.05) were found in the average scores of future thinking skills within the study sample attributed to the specialization variable (pure- applied), in favor of individuals with a pure.The study recommended the necessity of promoting a future thinking skills to the students. Furthermore, it is important to provide applied students with more time and opportunities to comprehend and solve various activities that enhance their thinking and apply future thinking skills.
Keywords: future thinking skills; Twelfth grade students